Fabrication and up-conversion fluorescence property of Er3+/Yb3+co-doped Ca-Si-Ti biomaterials. (16th January 2019) - Li, Xinfang; Li, Qin; Wang, Chaoyue; Ni, Jinqi; Zhang, Minhui; Chang, Jiang; Gao, Yanfeng; Yu, Jianding
Abstract: This work demonstrates bulk-type up-conversion biomaterials which could be used as a bone repair material with the ability to monitor bone mineralization. Er 3+ /Yb 3+ co-doped Ca-Si-Ti (CST3: TiO2 content is 30 mol%) bulk biomaterials were prepared via containerless processing technique in an aerodynamic levitation furnace and with subsequently heat treatment. The up-conversion fluorescence property was influenced by Yb 3+ doping concentration, heat-treatment and mineralization in simulated body fluid (SBF). Optimum emission intensities were obtained for the sample with 20 mol% of Yb 3+ doping concentration and heat treatment at 937 °C for 2 h. Hydroxyapatite (HAP) deposition was observed on the surface of the samples after soaking in SBF for 14 days, and the up-conversion fluorescence intensity of the samples decreased with the increase of soaking time. This indicates that Er 3+ /Yb 3+ co-doped CST3 materials are bioactive, in which the HAP mineralization in bone repair could be monitored by measuring the intensity change of up-conversion fluorescence.